Integrating ChatGPT in Islamic Higher Education: Enhancing Students’ Understanding of the Sustainable Development Goals - Shubhi Mahmashony Harimurti; Muhammad Sulaiman; Irfan Hilmi; Dwi Santosa Pambudi (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the optimality of learning by utilizing Chat GPT in Islamic Studies for Scholars courses to help students achieve the Sustainable Development Goals (SDGs). Specifically, Goals 4 (Quality Education), 5 (Gender Equality), 6 (Clean Water and Sanitation), 7 (Affordable and Clean Energy), 9 (Industry, Innovation, and Infrastructure), 11 (Sustainable Cities and Communities), 15 (Life on Land), 16 (Peace, Justice, and Strong Institutions), and 17 (Partnerships for the Goals). Pharmacy students are considered less responsive to Islamic history. This research is important to help students understand the SDGs, which are rarely understood by them. Islamic education for scholars, which mostly focuses on Islamic history, becomes too monotonous if it is only delivered in the classroom. Theoretical framework: Quran Surat al-Jumu'ah verse 10 serves as the theoretical framework for this research. Starting from a theoretical concept, it is then studied in a more practical context or put into practice. Literature review: A review of relevant literature reveals that lectures with practitioners can meet students' needs in understanding SDGs directly from experts. Method: Classroom Action Research is the method used in this study. Specifically, it is experimental and participatory. Innovations include involving practitioners in planning, teaching, and evaluating. Results: Students' lack of responsiveness was addressed by formulating problem-based learning or case studies to improve students' ability to solve problems and group-based projects. Field lectures with assignments to recreate historical sites using Chat GPT were found to increase student enthusiasm. An important finding of the study is that students were made aware of the SDGs by incorporating sustainable messages into the course content. Implications: Students' understanding of SDGs in the “Islam for Scholars” course is enhanced by combining theory and practice, using innovative technology, and encouraging active participation in the course. Novelty: The novelty of this research lies in the integration of learning content on the History of Islamic Civilization with SDGs. This is still rare in Indonesia and even globally.